OP06 Disability and uptake of screening for breast and bowel cancer in England. (13th September 2016) - Floud, S; Barnes, I; Verfurden, M; Kuper, H; Beral, V; Reeves, G; Green, J
Abstract : Background: In the USA disabled people have been found to be less likely than non-disabled to participate in cancer screening, but evidence from the UK is lacking. We investigated whether women in England who reported certain disabilities were less likely than other women to participate in routine screening programmes for breast and bowel cancer. Methods: In 2006/7, 683, 235 Million Women Study participants in England completed a questionnaire that included questions on disability. The participants were electronically linked to routinely collected NHS screening programme data. In 2006/7, the NHS Breast Screening Programme routinely invited women aged 50–70 every 3 years to attend a screening clinic for routine mammography, and the NHS Bowel Screening Programme invited people aged 60–69 every 2 years to carry out a routine faecal occult blood test using a home test. Analyses excluded women with previous cancer and included women in the eligible age range who had at least one subsequent invitation for routine screening (461, 063 women invited for breast screening and 460, 703 invited for bowel screening). Adjusted odds ratios (ORs) for uptake of screening were calculated for women reporting impairment of either mobility, self-care, hearing, visual or memory versus women reporting none of these disabilities. Results: Overall 22% of participants reported having impaired mobility, self-care, hearing, vision or memory. They were less likely to have been screened for breast or bowel cancer than women with no such disabilities (after adjustment for age, region of residence and area deprivation, OR for not being screened for breast cancer = 1.71, 95% CI 1.67–1.75 and OR for not being screened for bowel cancer = 1.55, 95% CI 1.52–1.57). When each type of disability was looked at separately, impairment in self-care and vision had the greatest effects (for self-care, breast OR = 2.43, 95% CI 2.33–2.52 and bowel OR = 1.91, 95% CI 1.86–1.96; and for vision, breast OR = 2.19, 95% CI 2.03–2.35 and bowel OR = 1.72, 95% CI 1.63–1.81). Conclusion: In England, women with disabilities, especially impaired self-care or vision, are less likely than other women to accept invitations for routine screening for breast or bowel cancer. They are less likely to be screened for breast than bowel cancer, possibly because breast screening involves tests done outside the home whereas bowel screening involves tests done at home.